Analisis Implementasi Kebijakan Pengendalian Huru Hara di Satuan Brimob Gorontalo: Perspektif Hukum Dan Keamanan Nasional - Bakari, Sadam; Moonti, Roy Marthen; Ahmad, Ibrahim (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The phenomenon of increasing potential for social conflict in the regions, including in Gorontalo Province, demands the presence of security forces that are able to act quickly, professionally, and in accordance with legal corridors. The Brimob unit as part of the National Police has a vital role in implementing riot control policies to maintain national stability and security. This research aims to analyze the effectiveness of Brimob Gorontalo's role in implementing the policy, in terms of legal aspects, especially in accordance with the principles of human rights and applicable laws and regulations. The approach used in this research is descriptive qualitative with literature and documentation study methods. The results of the analysis show that although the policy has been implemented in accordance with protap and regulations, the effectiveness of its implementation still faces challenges such as limited human resources, understanding of human rights, and social resistance. Therefore, it is recommended that Brimob Gorontalo strengthen human rights-based training, increase transparency of actions, and strengthen synergies with communities and local policy makers to create sustainable and equitable security.